Statistical analysis of the fluctuations of an initial-state model with independently distributed hot spots - Nicolas Borghini; Hendrik Roch; Alicia Schütte (European Physical Journal C: Particles and Fields)
Abstract We determine the uncorrelated modes that characterize the fluctuations in a semi-realistic model for the initial state of high-energy nuclear collisions, consisting of hot spots whose positions are distributed independently. Varying the number of hot spots, their size, and the weights with which they contribute to the initial state, we find that the parameter that has the largest influence on the relative importance of the fluctuation modes is the source size, with more extended hot spots leading to a more marked predominance of the principal modes.